Foods for Sleep Improvement: A Review of the Potential and Mechanisms Involved - Rui Fan; Yingmin Jia; Zhou Chen; Siting Li; Bing Qi; Aijin Ma (Foods)
Insomnia affects one-third of the world’s population; the negative effects of insomnia are significant, and traditional insomnia medications have numerous side effects and cause considerable suffering. This has aroused interest in obtaining sleep-improving substances from foods. This study conducted a comprehensive literature review using Web of Science and PubMed with keywords like “sleep”, “insomnia”, and “food”. A subsequent summary of the literature revealed that certain foods, including milk, Ziziphus jujuba, Lactuca sativa, ginseng, Schisandra chinensis, and Juglans regia, etc., are purported to enhance sleep quality by prolonging sleep duration, reducing sleep latency, and alleviating anxiety. The mechanisms of these foods’ effects mainly occur via the central nervous system, particularly the gamma-aminobutyric acid (GABA)ergic and 5-hydroxytryptamine (5-HT)ergic systems. Although this review supports the fact that they have potential, further research is needed. There are also issues such as more limited foods, fewer mechanisms, fewer pharmacokinetic studies, and more traditional research models being involved. These need to be addressed in the future to adequately address the problem of insomnia. It is hoped that this study will contribute to research into foods with sleep-improving properties and, in the future, provide an effective natural alternative for those seeking medication.